Comparison of social values between some Filipino and Chinese adolescents - Chao, Pei-te Sun 1921- ([Quezon City s.n.], 1966)
This study investigates the similarities and differences in social values between Filipino and Chinese adolescents both in the Philippines and in Taiwan, and the reasons that may influence the choices of ideals of Filipino and Chinese adolescents in the Philippines and in Taiwan.
Thesis (M.Ed.)--Univesity of the Philippines
Keywords: Social values; Adolescence